2009
DOI: 10.1016/j.devcel.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Exocrine Duct Cells Give Rise to Insulin-Producing β Cells during Embryogenesis but Not after Birth

Abstract: A longstanding unsettled question is whether pancreatic beta cells originate from exocrine duct cells. We have now used genetic labeling to fate map embryonic and adult pancreatic duct cells. We show that Hnf1beta+ cells of the trunk compartment of the early branching pancreas are precursors of acinar, duct, and endocrine lineages. Hnf1beta+ cells subsequent form the embryonic duct epithelium, which gives rise to both ductal and endocrine lineages, but not to acinar cells. By the end of gestation, the fate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
546
4
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 447 publications
(591 citation statements)
references
References 50 publications
(109 reference statements)
37
546
4
2
Order By: Relevance
“…HNF1b is expressed broadly through the foregut-midgut region at E8, and in the liver and both pancreas anlagens at E9.5 (Haumaitre et al, 2005). Solar et al (2009) showed that the early HNF1b-expressing pool is multipotent and can seed all three compartments: acinar, duct, and endocrine. During the secondary transition, HNF1b expression becomes confined to the duct/endocrine bipotent progenitor domain of the central epithelial cord (the ''mature trunk epithelium'' described below), and is also duct-restricted in the postnatal or adult organ (Solar et al, 2009).…”
Section: Hnf1b/tcf2mentioning
confidence: 99%
See 4 more Smart Citations
“…HNF1b is expressed broadly through the foregut-midgut region at E8, and in the liver and both pancreas anlagens at E9.5 (Haumaitre et al, 2005). Solar et al (2009) showed that the early HNF1b-expressing pool is multipotent and can seed all three compartments: acinar, duct, and endocrine. During the secondary transition, HNF1b expression becomes confined to the duct/endocrine bipotent progenitor domain of the central epithelial cord (the ''mature trunk epithelium'' described below), and is also duct-restricted in the postnatal or adult organ (Solar et al, 2009).…”
Section: Hnf1b/tcf2mentioning
confidence: 99%
“…Solar et al (2009) showed that the early HNF1b-expressing pool is multipotent and can seed all three compartments: acinar, duct, and endocrine. During the secondary transition, HNF1b expression becomes confined to the duct/endocrine bipotent progenitor domain of the central epithelial cord (the ''mature trunk epithelium'' described below), and is also duct-restricted in the postnatal or adult organ (Solar et al, 2009). In the absence of HNF1b, there is the transient formation of a dorsal pancreas ud that expresses Pdx1 and Mnx1, but these progenitors fail to expand.…”
Section: Hnf1b/tcf2mentioning
confidence: 99%
See 3 more Smart Citations